PENGARUH INFLASI DAN NILAI TUKAR RUPIAH (KURS) TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) DI BURSA EFEK INDONESIA PERIODE 2012 – 2022 - Ainur Rohmah, Fadila; Jamaludin (Journal of Research and Publication Innovation, 2024)
This study aims to determine the effect of Inflation and the Rupiah Exchange Rate (Kurs) on the Composite Stock Price Index (IHSG) at the Indonesia Stock Exchange for the period 2012 – 2022. The research method used in this study is quantitative research. The sampling method is purposive sampling with criteria set by the author. The data used is time series data for the period from January 2012 to December 2022. The data analysis technique uses multiple linear regression analysis with a significance level of 5%. Based on partial testing results, the Inflation variable does not have a significant effect on the Composite Stock Price Index (IHSG), while the Rupiah Exchange Rate (Kurs) variable partially has a positive and significant effect on the Composite Stock Price Index (IHSG). Simultaneously, it wsas found that there is a significant positive effect between Inflation and the Rupiah Exchange Rate (Kurs) on the Composite Stock Price Index (IHSG) at the Indonesia Stock Exchange.